Kinesiophobia Levels in Fibromyalgia Syndrome and the Relationship Between Pain, Disease Activity, Depression - Burhan Fatih KOÇYİĞİT and Mazlum Serdar AKALTUN (Archives of Rheumatology, 2020)
Objectives: This study aims to compare kinesiophobia levels between patients with fibromyalgia syndrome (FMS) and healthy volunteers and to investigate the factors associated with kinesiophobia in FMS. Patients and methods: This case-control study included 88 female patients with FMS (mean age 41.61 years; range 21 to 61 years) and 67 female healthy volunteers (mean age 41.34 years; range 19 to 59 years). The participants’ age, body mass index (BMI), and educational status were recorded. Patients were evaluated using a visual analog scale for pain, the Fibromyalgia Impact Questionnaire (FIQ) for disease activity, the Hamilton Depression Scale (HAM-D) for depression level, and the Tampa Scale for Kinesiophobia (TSK) for kinesiophobia. Additionally, the patients’ serum 25-hydroxyvitamin D levels were measured. Results: No significant differences were found between the patient and control groups in terms of age, BMI, and educational status (p>0.05). The mean TSK scores were 42.0±7.6 in the patient group and 37.2±8.8 in the control group. TSK score was significantly higher in the patient group (p<0.001). BMI levels, FIQ scores, and vitamin D concentrations were significantly associated with TSK scores according to the linear regression analysis (p<0.05). However, age, symptom duration, and HAM-D scores were not found to be associated with TSK scores (p>0.05). Conclusion: Kinesiophobia scores were significantly higher in patients with FMS. Physicians should focus on kinesiophobia when evaluating patients with FMS and inform patients about the importance and treatment strategies of kinesiophobia.